Heavyweight extension to the UML class diagram metamodel for modeling context aware systems in ubiquitous computing. Issue 3 (4th September 2017) - Boudjemline, Haider; Touahria, Mohamed; Boubetra, Abdelhak; Kaabeche, Hamza
Abstract : Purpose: The development of context-aware applications in ubiquitous environments depends not only on the user interactions but also on several context parameters. The handling of these parameters is a fundamental problem in these systems. The key purpose of this work is to enrich the unified modeling language (UML) class diagram with new constructs to provide a universal model capable of coping with the context-awareness concerns. Design/methodology/approach: The authors provide a review of existing context handling approaches. Afterward, they relied on the UML extensibility mechanisms to propose a heavyweight extension for the UML class diagram. This generic approach allows describing the different context parameters since the modeling phase. Findings: Existing solutions for context handling apply the contextual constraints on finished applications or tend to be dependent on a specific development process. This paper presents a solution based on UML, which allows dealing with context since the modeling phase, and independently of development processes. This proposal is implemented as an eclipse editor and illustrated through a case study in the healthcare field. Originality/value: This paper addresses the problem of context handling, and it presents a review of the foremost existing solutions. The paper also presents a heavyweight extension for the UML class diagram, which consists in enriching it with additional constructs, capable of monitoring how applications are linked to context parameters and how the values of these parameters may affect the application behavior.